Teaching Reading Comprehension in Narrative Text by Using SRE (Scaffolded Reading Experience) Strategy to the Second Semester Students of Baturaja University - Nopa Yusnilita (ELTE Journal (English Languange Teaching and Education), 2016)
ABSTRACT The problem of the study was significantly effective to teach reading comprehension in narrative text by using Scaffolded Reading Experience to the second semester students of Baturaja University. The objective of the study was to find out whether in teaching reading comprehension by using SRE strategy was significantly effective or not in the second semester students of Baturaja University.In conducting this study pre-experimental method was used. The population of this study is all of the students in second semester were 182 students that were taken by using cluster random sampling method. The data was collected by using written test and analyzed by using paired sample t-test analyzing.Based on the calculation, the mean score in pre-test was on the result of pre-test was 58.91 and post-test was 74.18, t-obtain was 15.473 in the significant level of 5% and df=37 (df=N-1) =36, the value of t-table was 1.69. It could be concluded that the use of SRE strategy in teaching reading comprehension in narrative text to the second semester students of Baturaja University. This strategy to helps students increases their reading comprehension skills. That this strategy could make reading not only beneficial for them but enjoyable as well and could increase the students’ reading comprehension achievement. Beside that the students also could successfully reading, understanding, learning from what they were reading, and enjoying the experience of reading from the text. Finally the students’ got better in reading subject.Key words: Teaching, Narrative Text, Scaffolded Reading Experience (SRE)